Pengembangan Bahan Ajar Multimedia Berbasis Flipbook Materi Perwasitan pada Mata Kuliah TP. Pembelajaran Tenis Lapangan - Ni Nyoman Ayu Pradnyani Putri Editha; I Gede Suwiwa; Peby Gunarto (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
This study aimed to develop a flipbook-based multimedia teaching material for the Tennis Learning course. The research employed a Research and Development (R&D) approach using the ADDIE model as the development framework, which consists of five stages: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The research subjects included students of the Physical Education, Health, and Recreation Study Program, Faculty of Sports and Health, Universitas Pendidikan Ganesha, as well as subject matter experts, instructional design experts, instructional media experts, and field practitioners. The product was evaluated through individual trials (3 students), small group trials (7 students), and large group trials (21 fourth-semester students). The validation results indicated feasibility percentages of 96% from the subject matter expert, 97% from the instructional design expert, 100% from the instructional media expert, and 97% from the field practitioner. Meanwhile, student trial results showed feasibility percentages of 97% in the individual trial, 96% in the small group trial, and 97% in the large group trial. Therefore, the flipbook-based multimedia teaching material on officiating in the Tennis Learning course was categorized as excellent and highly feasible for use as a supporting instructional resource in both classroom and field learning activities.